State Cabability in India - Somanathan, T V; Natarajan, Gulzar (UK Oxford University Press, 2022)
The deficiencies in the capability of the state to design and implement effective policies are arguably the biggest development challenge facing developing countries like India. This book seeks to assess state capability in India, identify weaknesses in policy design and programme implementation, and their causes, and propose some measures to remedy them. Importantly, it does so while recognizing political economy constraints and focusing predominantly on the administrative contributors. To this extent, the book's suggestions are practical enough for adoption by stakeholders at different levels.
Keywords: POLITICAL ASPECTS; Public institutions; Political planning